The women's heart health programme: a pilot trial of sex-specific cardiovascular management - Ting Ting Low; Siew Pang Chan; Shin Hnin Wai; Zhou Ang; Kyu Kyu; Kim Yee Lee; Anne Ching; Sarah Comer; Naomi Qiu Pin Tan; Elizabeth Grace Hui En Thong; Tracy Nang; Mohan Dutta; et al. (BMC, 2018)
Abstract Background There is increasing knowledge of sex-specific differences in cardiovascular disease and recognition of sex disparities in management. In our study, we investigated whether a cardiovascular programme tailored to the specific needs of women could lead to improved outcomes. Methods We randomised 100 female patients to receive cardiology follow-up with the conventional sex-neutral cardiac programme (control), or the sex-tailored Women's Heart Health Programme (intervention). The intervention group was managed by an all-women multidisciplinary team and received culture-centred health intervention workshops, designed through in-depth interviews with the participants. The primary outcome was cardiovascular risk factor improvement at 1 year. Secondary outcomes include cardiovascular event rates, quality of life scores, and self-reported improvement in knowledge, attitudes, intentions and practices. Generalised structural equation model analysis was used to determine if the intervention group had better outcomes at alpha level 0.1. Results The mean age was 67.3 ± 12.7 years, with an ethnic distribution of 70% Chinese, 18% Malays, and 12% Indians. The majority of these patients had no formal or primary level of education (63%), and were mostly unemployed (78%). Patients in intervention group had better control of diabetes mellitus (lower HbA1c of 0.63% [CI 0.21-1.04], p = 0.015) and lower body-mass-index (0.74 kg/m2 [CI 0.02-1.46], p = 0.092) at 1 year, but there was no significant difference in blood pressure or lipid control. Overall, there was a trend towards better risk factor control, 31.6% of intervention group versus 26.5% of control group achieved improvement in at least 1 CV risk factor control to target range. There was no significant difference in incidence of cardiovascular events, quality of life, or domains in knowledge, attitudes, intention and practices. Conclusion This pilot study is the first of its kind evaluating a new model of care for women with heart disease. The potential to improve outcomes needs to be studied in a larger trial with longer follow up. Trial registration This trial was prospectively registered clinicaltrials.gov on 6 May 2013. Trial Number: 2013/00088. Identifier: NCT02017470